A study of fluid forces acting on a foot during eggbeater kicks of water polo players - Kawai, E.; Tsunokawa, T.; Tsubakimoto, S.; Takagi, H. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The purpose of this study was to estimate fluid forces acting on a foot during eggbeater kicks of water polo players by the pressure-distribution-measuring method. Six male water polo players performed eggbeater kicks. Four pairs of pressure sensors were attached to the dominant foot to measure pressure distribution. Fluid-force vectors were calculated. The eggbeater kick cycles were divided into three phases (i.e. out-, in- and upkick phase) based on the knee joint angle and the displacement of the ankle. Maximum values and mean values of the propulsive component of fluid forces were 165.4 * 24.6 N and 38.2 * 4.6 N (mean i SD). Moreover, it was established that a swimmer mainly produces propulsive forces during out-kick and in-kick phases.